Mathematical model of “dialectical logic”, and relatively autonomous cognitive robots - Vladimir O. Lobovikov (Антиномии, 2019)
The object of investigation is the notorious problem of “dialectical-logic”, and its relevance to constructing relatively autonomous cognitive robots. The subjectmatter is formal axiological aspect of the mentioned object. The method is constructing and studying discrete mathematical models. Scientific novelty: for the first time such a formulation of the problem of “dialectical-logic” and such a psychologically unexpected solution of it are submitted, which make up a foundation for scientific investigation of possibility of modeling “dialectical-logic” of thinking by artificial intellectual systems. According to the conception developed in this paper, the meaning of the metaphorical expression “dialectical-logic” is formal axiology of thinking. Therefore, to model “dialectical-logic” by relatively autonomous cognitive robots, a discrete mathematical representation of the subject-matter of investigation is constructed, namely; a logically consistent system of equations of two-valued algebra of formal axiology which system models formal-axiological aspect of adequate thinking about objective contradictions of material world. Theoretic and practical significance of the obtained new scientific result is creating necessary prerequisites for constructing relatively autonomous cognizing robots.